Analisis Sistem Pencatatan Kartu Stok Obat di Puskesmas Batua Kota Makassar - Meliana Handayani; Irwandi Rachman; Andi Adhayana Akbar; Andi Atssam Mappanyukki; Wahyudin Wahyudin (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Recording drug stock cards is an important process in managing drug inventory at Batua Health Center, Makassar City. This study aims to evaluate the drug stock card recording system and its effectiveness in inventory monitoring. The methods used include in-depth interviews with informants, direct observation, and document analysis related to drug recording. The results showed that all aspects of the recording system were well fulfilled, reflecting a structured and accurate system, as well as the use of distribution books to verify the suitability of the data. Although the recording system was considered efficient, some informants recommended improvements in the layout of the storage space to increase accessibility. In conclusion, the application of technology in drug stock management needs to be improved to increase the efficiency and accuracy of inventory management at Puskesmas Batua.